The Impact of 30 Km/H Speed Limit Policy on Physical Activity– A Mixed-Methods Natural Experiment in Amsterdam, The Netherlands (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: In this mixed-methods natural experiment study, we evaluated the impact of a speed limit reduction policy (50 to 30 km/h) on physical activity (PA) outcomes in the city of Amsterdam.Methods: In Amsterdam, policy for a city-wide reduction to 30 km/h was implemented on December 8th, 2023. We conducted baseline (November 2023) and follow-up (November 2024) measurements in four intervention and two control sites, based on street-, neighbourhood- and SES-characteristics. We assessed PA and transport behaviour outcomes by inviting 9,679 households for the International Physical Activity Questionnaire (IPAQ) and systematic street observations using an adapted version of Method for Observing pHysical Activity and Wellbeing (MOHAWk). The latter provided additional insight into safety outcomes related to children (e.g. supervision). Changes in PA outcomes between intervention and control groups were analysed using a multilevel linear or negative binomial difference-in-difference analyses (as appropriate).Results: In the survey, a total of 618 residents (>18 years old) participated (55.1 ± 17.5 (standard deviation) years old). There were non-significant increases in self-reported leisure MVPA (97.53 min/week; 95% confidence interval (CI) = –1.09, 196.15), cycling for transport (94.97 min/week; 95% CI = –35.29, 225.23), walking for transport (75.05 min/week; 95% CI = –75.70, 225.80), walking for leisure (27.38 min/week; 95% CI = –62.09, 116.85). Similarly, there were non-significant decreases in self-reported time spent in a car (–35.65 min/week; 95% CI = –188.68, 117.39) and time spent sitting (–92.10 min/week; 95% CI = –556.50, 372.29). In street observations, we observed a total of 16,055 street users over 120 hours (47% adults, 23% children (